Are There Lower Repetition Priming Effects in Children with Developmental Dyslexia? Priming Effects in Spanish with the Masked Lexical Decision Task. Issue 2 (2nd April 2016) - Nievas-Cazorla, Francisco; Soriano-Ferrer, Manuel; Sánchez-López, Pilar
ABSTRACT: The aim of this study was to compare the reaction times and errors of Spanish children with developmental dyslexia to the reaction times and errors of readers without dyslexia on a masked lexical decision task with identity or repetition priming. A priming paradigm was used to study the role of the lexical deficit in dyslexic children, manipulating the frequency and length of the words, with a short Stimulus Onset Asynchrony (SOA = 150 ms) and degraded stimuli. The sample consisted of 80 participants from 9 to 14 years old, divided equally into a group with a developmental dyslexia diagnosis and a control group without dyslexia. Results show that identity priming is higher in control children (133 ms) than in dyslexic children (55 ms). Thus, the "frequency" and "word length" variables are not the source or origin of this reduction in identity priming reaction times in children with developmental dyslexia compared to control children.